An updated systematic review and meta-analysis of the effects of testosterone replacement therapy on erectile function and prostate - Xu, Zhunan; Chen, Xiangyu; Zhou, Hang; Ren, Congzhe; Wang, Qihua; Pan, Yang; Liu, Li; Liu, Xiaoqiang (Frontiers in Endocrinology, 2024)
Introduction: Testosterone replacement therapy (TRT) is a generally accepted method treating for aging-related late-onset hypogonadism (LOH). However, the efficacy and safety of TRT remain controversial. An updated systematic review and meta-analysis aimed to determine the effectiveness and security of TRT treating for LOH.Methods: Randomized controlled trials (RCTs) of TRT for LOH were searched in the databases of Pubmed, Embase, Clinicaltrials.gov and Cochrane from 1990 to 2023 and an updated meta-analysis was conducted.The results of 28 RCTs involving 3461 patients were included and scrutinized in this analysis. Among these, 11 RCTs were of long-term duration (≥12 months), while 18 RCTs were short-term studies (<12 months) comparing TRT with a placebo. TRT modalities comprised injection, oral administration, and transdermal administration. International Index of Erectile Function (IIEF) (Weighted Mean difference (WMD) 3.26; 95%; 95% confidence interval (CI) 1.65-4.88; P<0.0001) was obviously improved in the TRT group. International Prostate Symptom Score (IPSS) (WMD 0.00; 95% CI -0.45-0.45; P=1.0), Prostate Volume (PV) (WMD 0.38; 95% CI -0.64-1.41; P=0.46), Maximum Flow Rate (Qmax) (WMD 1.86; 95% CI -0.98-4.69; P=0.20), Postvoid Residual Urine Volume (PVR) (WMD 3.20; 95% CI -5.87-12.28; P=0.49) and Prostate-Specific Antigen (PSA) (WMD 0.08; 95% CI -0.00-0.17; P=0.06) were not significantly statistical between two groups.This meta-analysis reveals that TRT could improve the IIEF score of hypogonadal men without detriment to the IPSS score, PV, Qmax, PVR and PSA regardless of the administration method or duration of treatment.